2005
DOI: 10.1086/427474
|View full text |Cite
|
Sign up to set email alerts
|

The Gas‐Phase Deuterium Fractionation of Formaldehyde

Abstract: The dominant mechanism for the deuteration of formaldehyde in the gas phase of low-temperature interstellar cloud cores occurs via reaction with the deuterating ions H 2 D þ , HD þ 2 , and D þ 3 . Until now, it has been assumed that deuteration leads to an ion that, on recombination with electrons, can produce a deuterated neutral species with a statistical branching fraction. Quantum chemical calculations reported here, however, show an entirely different picture, in which the deuteration of formaldehyde lead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 36 publications
0
25
0
Order By: Relevance
“…Yet, except for ammonia and HNC, the direct destructive route is blocked for an assortment of reasons. First, consider H 2 CO. As shown by Osamura et al (2005), deuteration of formaldehyde leads to the ion H 2 COD + , with the deuterium on the opposite side of the molecule from the hydrogens. Dissociative recombination then leads just to H 2 CO + D rather than to HDCO + H, so that no deuteration is accomplished unless there is significant internal rearrangement during recombination, which is assumed not to be the case here.…”
Section: Secondary Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, except for ammonia and HNC, the direct destructive route is blocked for an assortment of reasons. First, consider H 2 CO. As shown by Osamura et al (2005), deuteration of formaldehyde leads to the ion H 2 COD + , with the deuterium on the opposite side of the molecule from the hydrogens. Dissociative recombination then leads just to H 2 CO + D rather than to HDCO + H, so that no deuteration is accomplished unless there is significant internal rearrangement during recombination, which is assumed not to be the case here.…”
Section: Secondary Speciesmentioning
confidence: 99%
“…Not only singly deuterated isotopologues are produced by secondary reactions involving deuterated ions; species such as NHD 2 , ND 3 , and D 2 CO are observed and understood at least partially in terms of gas-phase syntheses (Roberts & Millar 2000;Gerin et al 2006;Osamura et al 2005;Roueff et al 2005). Although H + 3 is not the only important molecular ion to exchange deuterons with HD exothermically and rapidly, it is the most abundant under most conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The hydrogenation of the unstable radicals HCO and CH 3 O into H 2 CO and CH 3 OH, respectively, is believed to take place quickly, whereas the formation of these radicals from CO and H 2 CO has a barrier (about 2500 K and 2200 K, respectively − Garrod et al 2008;Osamura et al 2005), according to both theoretical calculations and experiments (Peters et al 2013;Wang et al 1973) 3 . It is therefore likely that H atoms arriving on the grain surface will usually react with HCO or CH 3 O rather than with CO or H 2 CO, leading to the most stable products.…”
Section: Grain Surface Formation Routementioning
confidence: 99%
“…We included the major gaseous D-exchange reactions of the UMIST database (McElroy et al 2013), the major surface reactions identified by Stantcheva & Herbst (2003), and gas-phase reactions related to HDO using the approach of Aikawa et al (2012). The initial chemical abundances were adopted from Garrod et al (2007), and include the initial abundance [HD] = 1.5 × 10 −5 × [H 2 ] (Osamura et al 2005).…”
Section: Chemical Modeling Of Abundancementioning
confidence: 99%